Factors affecting farmers' decision to use organic fertilizers on Robusta coffee plantation: A case study in Tanggamus, Lampung. Issue 1 (January 2022) - Hasibuan, A M; Ferry, Y; Wulandari, S
Abstract: The dependency on agri-chemical inputs, such as fertilizers and pesticides, tends to increase among small-scale farmers in developing countries. On the other hand, demand for organic products, including coffee, continuously increases due to the rising concern of the consumers for sustainable products and a healthy lifestyle without chemical residues. This study aims to understand the determinant factors that affect small-scale farmers in using organic fertilizers. The research was conducted in Tanggamus Regency from June – August 2019 using a survey method. Respondents were determined using a simple random sampling method. Data were analyzed using descriptive statistics and a linear regression model. The results showed that the use of organic fertilizers is still limited and farmers tend to use chemical fertilizers to maintain their coffee plants. The dose of inorganic fertilizer and ownership of the number of coffee trees have a negative effect on the application of organic fertilizer. While the experience of farmers in coffee farming and the age of coffee plants have a positive effect on the dose of organic fertilizer applied.